The Spatial Dimension of Local Governments’ International Relations at the Voivodship Level - Szmigiel, Katarzyna (Journal of Public Governance, 2018)
The paper presents an analysis of the convergence in the geographical directions of regional governments’ international relations. The analysis is based on documents for cooperation and a range of projects implemented under the European territorial cooperation. The paper has, above all, a practical dimension. The convergence of these two forms of cooperation on the international arena might be a condition sine qua non of a success of the activities previously implemented under the documents for cooperation. It results from the accessibility of financial resources offered toPolish administrative regions. In its theoretical dimension, the paper discusses the basic terminology of international relations of non-central governments.